Establishment of Intellectual Disability Students’ Employee Responsibilities as Cleaning Service at the Post-School Periode “Ethnographic Study at SLB Pembina National in the level section C” - Abdul Adim (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
From preliminary study and observation for intellectual disability students as cleaning service from post-school SLB Pembina Nasional C Malang, they work spiritly, disciplinely and in good and satisfied customer. The research was qualitative approach of ethnography type through interview, observation and documentation to describe how the formation of employee responsibilities of post-school intellectual disability as cleaning service? There were 3 cleaning servicer as research subject. The objectives of the research were to describe: (1) the skill training program (2) the concept of skill trainer (3) the form of supervision conducted. and (4) the form of the employee responsibilities of the intellectual disability students at the post-school periode as cleaning service. The results of the informant interviews were that: (1) the training program as cleaning service skill provided was according to the children’s interest and potential, (2) the concept of trainer in giving the material and the method used was easy, fun and workable, (3) the touch supervision involving teachers, parents, and routine supervision programs make the children obedient and happy as cleaning service, (4) the formation of employee responsibilities of post-school intellectual disability students as a devoted, discipline and hard worker cleaning service with satisfactory results. The advice for principals to provide confidence for post-school intellectual disability on various types of cleaning service jobs, and not limited to only types of work outside the building (field).Dari studi pendahuluan dan observasi untuk siswa tuna grahita sebagai cleaning service sebagai bagian dari program pasca sekolah dari SLB Pembina Nasional C Malang, mereka bekerja dengan semangat, disiplin dan baik dan puas dalam pelayanan. Penelitian ini menggunakan pendekatan kualitatif jenis etnografi melalui wawancara, observasi dan dokumentasi untuk menggambarkan bagaimana pembentukan tanggung jawab kerja anak tuna grahita cleaning service? Ada 3 cleaning service sebagai subjek penelitian. Tujuan dari penelitian ini adalah untuk mendeskripsikan: (1) program pelatihan ketrampilan (2) konsep pelatih keterampilan (3) bentuk pengawasan yang dilakukan dan (4) bentuk tanggung jawab kerja siswa tuna grahita pada program masa pasca sekolah sebagai cleaning service. Hasil wawancara terhadap informan adalah: (1) program pelatihan sebagai keterampilan cleaning service yang diberikan sesuai dengan minat dan potensi anak, (2) konsep pelatih dalam memberikan materi dan metode yang digunakan pun mudah, menyenangkan dan dapat dikerjakan, (3) pengawasan yang menyentuh yang melibatkan guru, orang tua, dan program pengawasan rutin membuat anak taat dan bahagia sebagai petugas kebersihan, (4) pembentukan tanggung jawab kerja siswa tuna grahita pasca sekolah sebagai pembina yang berdedikasi, disiplin dan pekerja keras, pelayanan dengan hasil memuaskan. Saran bagi kepala sekolah untuk memberikan rasa kepercayaan diri pada anak tuna grahita pada program pasca sekolah pada berbagai jenis pekerjaan sebagai cleaning service, dan tidak terbatas hanya pada jenis pekerjaan di luar gedung.